PHYTOCHEMICAL TEST AND TOXICITY (Brine Shrimp Lethality Test) IN ETHANOL EXTRACT, ETHYL ACETATE FRACTION AND RESIDUAL ETHANOL FRACTION OF AJERAN LEAVES (Bidens pilosa L.) - Audia, Nuraini Meti; -, Daniel; Marliana, Eva (Jurusan Kimia FMIPA UNMUL, 2020)
Phytochemical test and toxicity in ethanol extract, ethyl acetate fraction and residual ethanol fraction of ajeran leaves (Bidens pilosa L.) has been done. The method used to determine secondary metabolites is clualitative test and the value of Lethal Concentration (LC50) with the Brine Shrimp Lethality Test (BSLT). Phytochemical test results showed that the ethanol extract and ethyl acetate fraction contained flavonoid, steroid and phenol compound. Residual ethanol fraction contained flavonoid and phenol compound. Toxicity test showed ethanol extract had LC50 value of 862.19 ppm. Ethyl acetate fraction has LC50 value of 8.26 ppm. Residual ethanol fraction had LC50 value of 275.24 ppm. The results of the toxicity test can be concluded that the ethyl acetate fraction very toxic category, ethanol extract and residual ethanol fraction included toxic category. The results that obtained from GC-MS characterization were steroid